International Child Abduction: Bagaimana Indonesia Meresponnya? - Penasthika, Priskila Pratita; Arijati, Lita; Anggriana, Annissa Gabianti (Jurnal Hukum & Pembangunan, 2018)
Wrongful removal or retention of a child outside the state of his or her habitual residence is known as international child abduction. The Hague Convention on the Civil Aspects of International Child Abduction 1980 established procedures to ensure the prompt return of the internationally abducted child to the state of his or her habitual residence. By discussing the international child abduction cases involving Indonesia, this article demonstrates the obstacles in returning those internationally abducted children. This discussion is undertaken by taking into account the difference in qualifying the concept of international child abduction in Indonesian law and the Hague Convention 1980.